TEACHER PERFORMANCE ASSESSED FROM LEADERSHIP QUALITY, WORK EXPENSE, COMMUNICATION AND COMPETENCY (Study at the Surakarta Batik Education Foundation) - Safi'i Safi'i; Istiatin Istiatin; Supawi Pawenang (ITB AAS INDONESIA Surakarta, 2021)
This research took place at the Surakarta Batik Education Foundation. This type of research is a quality or correlational relationship which will explain the asymmetrical relationship between the variables studied. The research sample was 74 teachers of the Surakarta Batik Education Foundation. Collecting data using questionnaires, interviews, observation and documentation. The data analysis technique used multiple regression test, F test, t test, and determination test (R2). The results showed: 1) There is an effect of leadership quality, workload, communication and teacher competence together on the teacher performance of the Surakarta Batik Education Foundation. Thus, the better the quality of leadership, workload, communication and teacher competence, the better the performance of teachers at the Surakarta Batik Education Foundation. 2) There is an effect of leadership quality on teacher performance. Thus, the better the quality of leadership, the higher the performance of teachers at the Surakarta Batik Education Foundation. 3) There is an effect of workload on teacher performance. Thus, the better the level of workload, the higher the performance of teachers at the Surakarta Batik Education Foundation. 4) There is an effect of communication on teacher performance. Thus, the better the level of communication, the higher the performance of teachers at the Surakarta Batik Education Foundation. 5) There is an effect of competence on teacher performance. Thus, the better the level of competence, the higher the performance of teachers at the Surakarta Batik Education Foundation. Keywords: leadership quality, workload, communication, competence, and teacher performance.